THE IMPACT OF EXPERIENTAL MARKETING AND REPURCHASE INTENTION THROUGH CUSTOMER SATISFACTION IN COFFEE INDUSTRY - Friesa Ergo M; Santirianingrum Soebandi; I. G. A Aju Nitya Dharmani (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2020)
The objective of this research is to evaluate the inter-relationship among the experiental marketing, customer satisfaction and repurchase intention in the context of restaurant or cafe in Indonesia. A total of three hypotheses will be tested. A quantitave research will be carried out to address the research objective. Purposive sampling technique and the distribution of a total 187 responden will be selected as part of the research methodology specially in customer of Janji Jiwa Jilid 358 Surabaya. The statistical data will be analyzed by SEM-PLS. And the result shows that experiental marketing has positive effect on repurchase intention. Also indicates that the positive effect has been fully mediated by the customer satisfaction of the customer at Janji Jiwa Jilid 358 Surabaya. According to the conclusions, this research provides that sense and feel experiences are positively related to the repurchase intention as well as experiental marketing is positvely related to the customer satisfaction.